Exchange Rate Pass-Through into Import Prices - Campa, José Manuel; Goldberg, Linda S. (The Review of Economics and Statistics, 2005)
We provide cross-country and time series evidence on the extent of exchange rate pass-through into the import prices of 23 OECD countries. We find compelling evidence of partial pass-through in the short run, especially within manufacturing industries. Over the long run, producer-currency pricing is more prevalent for many types of imported goods. Countries with higher rates of exchange rate volatility have higher pass-through elasticities, although macroeconomic variables have played a minor role in the evolution of pass-through elasticities over time. Far more important for pass-through changes in these countries have been the dramatic shifts in the composition of country import bundles.